THE DIFFERENCE BETWEEN THE CONCEPT OF JUSTICE IN THE CONSTITUTION OF AFGHANISTAN AND THE REPUBLIC OF KAZAKHSTAN - Х. Мохаммади; С.Б. Бейсебаева; А.С. Сабыр; Б.Е. Тлеулов; Г.Т. Муратова (Хабаршы. Заң сериясы)
The pursuit of justice has remained a fundamental but elusive goal throughout human history, often subject to interpretation and debate among scholars of philosophy and law. Many countries enshrine the principle of justice in their constitutions, yet its precise meaning and application vary widely. In the constitutions of nations like the Republic of Kazakhstan and the Islamic Republic of Afghanistan, the concept of "justice" is notably vague, lacking clear definition or foundational research. In a recent research paper, the author undertook an examination of justice as articulated in the constitutions of Afghanistan and Kazakhstan. Employing a librarian method for information gathering and utilizing comparative analysis, the author sought to elucidate the understanding and treatment of justice within these constitutional frameworks. The findings of this investigation reveal a nuanced picture. In both cases, the concept of justice appears to prioritize the fairness of legal texts over their practical implementation. However, a notable distinction arises in the Constitution of Kazakhstan, where emphasis seems to be placed on actualizing justice rather than merely espousing its principles in legal documents. This brief comparison underscores the complexities inherent in conceptualizing and realizing justice within constitutional frameworks. It highlights the need for further research and analysis to bridge the gap between legal theory and practical application in the pursuit of justice within diverse socio-political contexts.